Glossary of plant derived insect deterrents - Jacobson, Martin, 1919- ([Place of publication not identified], CRC Press, 2017)
This handbook brings together in one place sources which entomologists, chemists, botanists, insect ecologists, physiologists, and pharmacologists may consult for information to supplement that reported herein on the subject of plant-derived feeding deterrents.
OCLC-licensed vendor bibliographic record.
Keywords: SCIENCE / Life Sciences / Botany; SCIENCE / Life Sciences / General; Botanical insecticides; Insecticidal plants; Insect baits and repellents